2008
DOI: 10.1057/palgrave.jibs.8400357
|View full text |Cite
|
Sign up to set email alerts
|

The motives for international acquisitions: capability procurements, strategic considerations, and the role of ownership structures

Abstract: Multinationals can start up greenfield entities or acquire existing firms to enter foreign nations. Regardless of the choice of greenfield investment vs acquisition, they can control full equity (i.e., wholly owned subsidiaries) or share ownership with local partners (i.e., joint ventures). Depending on the stake taken in the targets, therefore, international acquisitions can be classified into two major categories – full or partial – although this distinction is missing in most previous studies. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(161 citation statements)
references
References 31 publications
3
154
0
Order By: Relevance
“…The resource-based view literature suggests that capabilities and resources are the key determinants of a firm's competitive advantage (Barney, 1991). According to this resource-based theory, the key motivation for foreign acquisitions is to gain access to strategic assets such as natural resources, product differentiation, patent-protected technologies, superior managerial and marketing skills, as well as achieving economies of scale (Accenture, 2006;Athreye & Kapur, 2009;Chen, 2008;Cui & Jiang, 2010;Deng, 2007;Deng, 2009;Kumar, 2009;Rui & Yip, 2008;Wang & Boateng, 2007). Lacking such strategic resources, EM firms use cross-border M&As as the most effective way to improve their competitive advantage and performance (Gubbi, et al, 2010).…”
Section: Motives For Cross-border Mandasmentioning
confidence: 99%
See 1 more Smart Citation
“…The resource-based view literature suggests that capabilities and resources are the key determinants of a firm's competitive advantage (Barney, 1991). According to this resource-based theory, the key motivation for foreign acquisitions is to gain access to strategic assets such as natural resources, product differentiation, patent-protected technologies, superior managerial and marketing skills, as well as achieving economies of scale (Accenture, 2006;Athreye & Kapur, 2009;Chen, 2008;Cui & Jiang, 2010;Deng, 2007;Deng, 2009;Kumar, 2009;Rui & Yip, 2008;Wang & Boateng, 2007). Lacking such strategic resources, EM firms use cross-border M&As as the most effective way to improve their competitive advantage and performance (Gubbi, et al, 2010).…”
Section: Motives For Cross-border Mandasmentioning
confidence: 99%
“…Chinese MNEs are more interested in gaining natural resources and superior managerial and marketing skills in order to improve their competitive advantage in manufactured products (Athreye & Kapur, 2009;Chen, 2008;Cui & Jiang, 2010;Deng, 2007;Deng, 2009;Kumar, 2009;Rui & Yip, 2008;Wang, et al, 2012;Wang & Boateng, 2007), whereas cross-border acquisitions from Indian companies primarily involve a technologyintensive industry (e.g. software and pharmaceutical) in which India has a high competitive advantage (Arora, Arunachalam, Asundi, & Fernandes, 2001;Ethiraj, Kale, Krishnan, & Singh, 2005;Miozzo & Grimshaw, 2008;Sun, et al, 2012).…”
Section: Competitive Advantage and Performancementioning
confidence: 99%
“…Chen andHennart 2002, 2004;Jakobsen and Meyer 2008). We performed robustness tests with alternative levels of full ownership (90% and 100%).…”
Section: Variables Descriptions and Operationalizationmentioning
confidence: 99%
“…Jakobsen and Meyer (2008) on the other hand found that in transition economies MNEs engage in partial acquisitions to gain legitimacy and prevent powerful local stakeholders from hijacking the M&A deal. Chen (2008) suggested that partial CB M&As are mostly chosen as a means for capacity control in mature industries and speedy entry into rapidly growing markets. The most recent study by Contractor and colleagues (2014) applies the concept of 'distance' to explain the variation in cross-border acquisition equity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Location-specific resources include local organizationally embedded resources such as distribution networks and brand names, and local market embedded resources, such as local market experience and managerial knowledge. The nature of firms" existing resources determines whether they need to engage in such resource augmentation when investing abroad [42][43]. Since firms may be restricted in their structural and experiential resources to operate in a foreign market [8], and if their core competences are also based on location-specific resources, they need to augment the location-specific resources to overcome foreignness of liability and maintain competitive advantage in the host country.…”
Section: Resource-based View and Entry Modesmentioning
confidence: 99%